Trust and Online Privacy Concerns in a General Population of Internet Users - Stylianou, Stelios (My University, 2024)
Even though research on online privacy has been accumulating for the last two decades, the etiology of online privacy concerns is still open to more inquiry. The present study investigates whether and to what extent online privacy concerns are affected by trust, a variable that has received limited dedicated attention in this respect. Using data from a telephone survey of a representative sample of the general population of Internet users in a Mediterranean society, the study models trust in people and trust in institutions as the focal predictors of Internet users’ concerns about online privacy violations by other people, corporations, and governments. Five hypotheses are tested using multiple regression equations with several controls, including measures of offline and online social capital, digital literacy, length of Internet use, and privacy violation experience. The study concludes that trust, independently and consistently, albeit mildly, reduces online privacy concerns.
Keywords: Digital literacy; General population survey; Online privacy concerns; Privacy violation; Social capital; Trust in institutions; Trust in people